Determining of knowledge sharing - Selamat, Sarah Mardhiah; Abd Hamid, Roslina (2017)
Knowledge sharing is the process of transform individual knowledge to organizational knowledge which can helps the organization to get maximum outcomes from the employees.The purpose of conducting this study was to identify the determinants of knowledge sharing in Universiti Sains Malaysia (USM) Penang.132 out of 351 respondents in USM participated in this study. Data has been analyzed by using SPSS software and the results found that three variables i.e. rewards, self-efficacy and shared goals have significant relationship with knowledge sharing. To conclude, emphasizing on the right determinants of knowledge sharing will motivate the employees to share the relevant knowledge with superiors, colleagues and subordinates.Introduction - Recently, knowledge sharing has become the subject that attracts researchers to explore.Knowledge is recognized as useful information to gain competitive advantage and sustainability in organization.Thus, the organization must ensure that knowledge sharing is occurred actively and become a culture which foster on mutual giving and receiving knowledge.The latter of sharing knowledge will be beneficial to the employees and organization in terms of productivity improvement and cost efficiency (Blair, 2002). Knowledge sharing or the contributions by individuals to the collective knowledge of an organization (Cabrera & Cabrera, 2002), is increasingly acknowledged as an important research topic. According to Lu, Leung and Koch (2006), knowledge is often shared among the employees in the organization in various forms and the main objective of sharing knowledge is to transform individual knowledge into organizational knowledge. Knowledge sharing is crucial whereby it is a fundamental root of the organization establishment.There were many research conducted to determine the factors of knowledge sharing in private sectors.However, knowledge sharing interventions in public sectors are lacking of attention (Cong & Pandya, 2003). Furthermore, in public sectors, rewarding employees are subject to government allocation controlled by the federal government.Previous research has discovered many factors that have relationship with knowledge sharing.Gray (2001); Jeon, Kim and Koh (2011); and Kankanhalli, Bernard, and Wei (2005); found that perceived consequences, social factors, facilitating conditions, perceived reputation enhancement,perceived enjoyment in helping others, trust, perceived loss of knowledge power and shared goals lead to the culture of knowledge sharing.Despite variables tested by the mentioned scholars, the researcher came across with other variables to be tested i.e. culture, reciprocal relationship, reward, self-efficacy and shared goals.